Essen Stroke Risk Score Predicts Clinical Outcomes in Heart Failure Patients with Preserved Ejection Fraction: Evidence from the TOPCAT trial - Zhu, Wengen; Cao, Yalin; Ye, Min; Huang, Huiling; Wu, Yuzhong; Ma, Jianyong; Dong, Yugang; Liu, Xiao; Liu, Chen; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2022)
Background Heart failure (HF) with preserved ejection fraction (HFpEF) is associated with increased risks of stroke and other adverse outcomes.Aims This study sought to determine whether the Essen Stroke Risk Score (ESRS) could predict the risks of adjudicated clinical outcomes in patients with HFpEF from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial.Methods We evaluated associations of baseline ESRS with clinical outcomes by using the Cox proportional hazard model with competing risk regression. The diagnostic accuracy of the ESRS was assessed using the C-index and calibration data.Results Of 3,441 HFpEF patients with a mean follow-up of 3.3 years, the risk of stroke ranged from 0.32% per year at an ESRS of 1 to 2 points to 1.71% per year at a score of ≥6 points. Each point increase in ESRS was associated with increased risks of primary composite outcome (hazard ratios [HRs] = 1.31; 95% confidence intervals [CIs]: 1.23–1.40; C-index = 0.68), stroke (HR = 1.33 [95% CI: 1.16–1.53]; C-index = 0.68), myocardial infarction (HR = 1.60 [95% CI: 1.40–1.83]; C-index = 0.75), HF hospitalization (HR = 1.30 [95% CI: 1.20–1.41]; C-index = 0.71), any hospitalization (HR = 1.20, 95% CI: 1.15–1.26; C-index = 0.68), cardiovascular death (HR = 1.32 [95% CI: 1.20–1.44]; C-index = 0.68), and all-cause death (HR = 1.37, [95% CI: 1.28–1.48]; C-index = 0.68). The calibration curves showed that the ESRS had a better agreement between predicted and observed stroke risks compared with the R2CHADS2, CHADS2, or CHA2DS2-VASC stroke scores.Conclusion The ESRS had modest discriminatory abilities for predicting stroke as well as other adverse outcomes including myocardial infarction, hospitalization, and death in HFpEF patients. ESRS might have better calibration performance than R2CHADS2, CHADS2, or CHA2DS2-VASC in HFpEF at high risk for stroke.Clinical Trial Registration URL: https://clinicaltrials.gov. Unique identifier: NCT00094302.
Keywords: heart failure; stroke; adverse outcomes; Essen Stroke Risk Score; risk prediction